Diagnosing observed extratropical stationary wave changes in boreal winter - Sun, Wanying; Wang, Lei (Environmental research letters, 2023)
Stationary waves are time-averaged zonally asymmetric component of the climatological mean atmospheric circulation, primarily due to the unevenly distributed topography and diabatic heating. Stationary waves are subject to influence from long-term external forcing. In this study, the temporal evolution of the winter (January) Northern Hemisphere stationary waves during 1961–2020 is diagnosed with the fifth generation European Centre for Medium-range Weather Forecasts reanalysis data (ERA5), which shows an overall strengthening in amplitude and an eastward shift in phase. A stationary wave model is used to attribute the stationary wave response to changes in the zonal mean basic state (Δ ZM ) and the zonally asymmetric diabatic heating forcing ( Δ q ∗ ). The pattern of stationary wave changes is well captured by the response to Δ ZM alone, whereas the contribution of Δ q ∗ to the amplitude increases in height and becomes dominant in the stratosphere. Δ q ∗ is also found to be important in driving stationary wave changes in the North Pacific and Western Europe regions. Furthermore, changes in tropospheric stationary waves are probably a result of internal variability, whereas stratospheric changes are more likely to be driven by external forcing.